STUDI KELAYAKAN YELLOWCAKE HASIL SAMPING PETROKIMIA GRESIK SEBAGAI BAHAN BAKU PROSES PEMURNIAN DAN KONVERSI DI FASILITAS PILOT CONVERSION PLANT - Saputra, Ade; Yusnitha, Erilia; Abdurrosyid, Imam; Langenati, Ratih (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The Pilot Conversion Plant (PCP) facility has been successfully used for the purification and conversion of commercial yellowcake from Cogema – France. Thus, to support self-reliance of the nation, an assessment of the purification and conversion process of domestic yellowcake was carried out. One of domestic sources of yellowcake is the by-product of a process carried out at Petrokimia, Gresik. This study was carried out by comparing the characteristics of the chemical and physical properties of Petrokimia's yellowcake to those of Cogema's yellowcake which has been used at the PCP. Primary information was obtained from analysis results while secondary information was obtained from related literatures. The information obtained is also used to determine the process parameters needed by the PCP for the purification and conversion process. The results of this study show that Petrokimia's yellowcake is suitable to be used as the feed of purification and conversion process at the PCP facility. In addition, Petrokimia's yellowcake is easier to handle although requires more nitric acid than Cogema yellowcake dissolution. The parameters values of Petrokimia's yellowcake purification and conversion process that have been obtained include dissolution of yellowcake, purification of uranyl nitrate, uranyl nitrate concentrating, precipitation of uranyl nitrate into ammonium diuranate (ADU), drying of ADU powder, calcination of ADU into U3O8 powder and reduction of U3O8 powder into UO2 powder, which are no different from the parameters values for Cogema's yellowcake processing.